Development of a Regional Nursing Research Partnership for Academic and Practice Collaborations - Heather L. Tubbs-Cooley; Donna S. Martsolf; Rita H. Pickler; Caroline F. Morrison; Cassie E. Wardlaw (Nursing Research and Practice)
Background. Collaborative nursing research across academic and practice settings is imperative to generate knowledge to improve patient care. Models of academic/practice partnerships for nursing research are lacking. This paper reports data collected before and during a one-day retreat for nurse researchers and administrators from local universities and health care organizations designed to establish a regional nursing research partnership. Methods. Quantitative and qualitative methods were used to address the study aims: (1) to assess research involvement and institutional research resources; (2) to assess interest in and concerns regarding cross-institutional collaborations; and (3) to describe perceptions of the purpose of a partnership and resources needed to ensure success. Results. Participants (n=49) had differing perceptions of accessibility to resources; participants in practice settings reported less accessibility to resources, notably grant development, informatics, and research assistant support. Participants were interested in collaboration although concerns about conflict of interest were expressed. Four themes related to partnering were identified: harnessing our nursing voice and identity; developing as researchers; staying connected; and positioning for a collaborative project. Conclusion. Academic-practice research collaborations will become increasingly important with health care system changes. Strategies to develop and sustain productive partnerships should be supported.